Development of a Strategy for the Analysis of the Fluid Dynamic Behavior of Sieve Trays for Distillation - Paredes-Ortiz, Jose Alfredo; Rodríguez-Angeles, Mario Alberto; Vishwakarma, Vineet; Schubert, Markus; Hampel, Uwe; Gómez-Castro, Fernando Israel; May-Vázquez, Mayra Margarita (Computer Aided Chemical Engineering, 2024)
An Eulerian-Eulerian model was applied to simulate the two-phase flow behaviour in a sieve tray column, i.e., typically used for distillation. Following grid independence, the phase fraction was simulated, which exhibit good agreement with experimental data, especially in the liquid-dominant zones of the two-phase dispersion. In the upper gasdominant dispersion regions, a slight deviation of less than 10% was observed in the gas fraction data. The results demonstrate that the proposed modeling strategy can adequately predict the fluid dynamic behaviour in tray-equipped distillation columns.